Assessment of gasoline direct injector fouling effects on fuel injection, engine performance and emissions. (15th June 2018) - Badawy, Tawfik; Attar, Mohammadreza Anbari; Xu, Hongming; Ghafourian, Akbar
Graphical abstract: Highlights: Effects of injector tip deposits on spray dynamics and atomization were studied. Effects of injector tip deposits on charge inhomogeneity were investigated. Effects of the injector tip deposit on engine performance and emissions were investigated. Abstract: The current optical and thermal experimental tests were mainly focused on obtaining a comprehensive understanding of the effects of gasoline direct injector fouling on mass flow rates, spray characteristics, engine emissions and engine performance. A robust injector fouling cycle was employed to produce coked injectors in a multi-cylinder thermal engine. Deposit build-up in the coked injectors and fouling cycle repeatability was first examined by measurements of fuel flow rate. Macroscopic spray characteristics of the clean and the coked injectors were carried out using high-speed imaging and Planar Laser Induced Fluorescence (PLIF) of sprays foot-print. Fuel droplets size and velocity were characterised with a two-dimensional Phase Doppler Particle Analyser (PDPA). It was observed that the deposit build-up inside injector nozzles and on injector tips reduced the plume cone angle while increased plume penetration length, plume separation angles, mean droplet velocity and size for the coked injector. Impact of injector fouling was further investigated by PLIF measurements of in-cylinder charge inhomogeneity and repeatability in mixture preparation. The coked injectors showed higher degree of inhomogeneity and poorer repeatability in mixture preparation. These were in agreement with combustion analysis results where the coked injectors showed lower load and lower combustion stability compared with the clean injector under same operating conditions. Significantly higher unburned hydrocarbon emissions and particulate number concentration were also observed for the coked injectors. This work was carried out to obtain a broad picture of injector cooking effects in GDI engines.